Solve for z s=rz+sz

Math
s=rz+sz
Rewrite the equation as rz+sz=s.
rz+sz=s
Factor z out of rz+sz.
Tap for more steps…
Factor z out of rz.
zr+sz=s
Factor z out of sz.
zr+zs=s
Factor z out of zr+zs.
z(r+s)=s
z(r+s)=s
Divide each term by r+s and simplify.
Tap for more steps…
Divide each term in z(r+s)=s by r+s.
z(r+s)r+s=sr+s
Cancel the common factor of r+s.
Tap for more steps…
Cancel the common factor.
z(r+s)r+s=sr+s
Divide z by 1.
z=sr+s
z=sr+s
z=sr+s
Solve for z s=rz+sz

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top